2003
DOI: 10.1103/physrevb.68.104426
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic ordering and spin-liquid state ofYMnO3

Abstract: We have measured the bulk properties as well as the elastic and inelastic neutron scattering of YMnO 3 in order to understand the static and dynamic properties of the Mn moments. Our measurements clearly show that above T N there are short range correlations between spins at the nearest neighbor and next nearest neighbor Mn sites, which also fluctuate in time. This, together with other bulk properties, demonstrates the presence of a spin liquid phase above T N arising from the geometrically frustrated Mn momen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
100
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 22 publications
(13 reference statements)
12
100
1
3
Order By: Relevance
“…Most such approaches essentially involve fitting a simple form for the radial spin correlation function to the powder data. In these methods, the connectivity of the crystal structure is not considered; instead, either the magnitude of the spin correlations is fitted for a one-dimensional list of atomic separations (see, e.g., [14,15]), or the diffuse features are fitted to a broad peak-shape function to estimate the spin correlation length (see, e.g., [16]). However, the crystal structure plays no less significant a role in paramagnets than in ordered magnets: indeed, in a paramagnet the crystal structure completely determines the symmetry and periodicity of the diffuse scattering pattern [17].…”
Section: Introductionmentioning
confidence: 99%
“…Most such approaches essentially involve fitting a simple form for the radial spin correlation function to the powder data. In these methods, the connectivity of the crystal structure is not considered; instead, either the magnitude of the spin correlations is fitted for a one-dimensional list of atomic separations (see, e.g., [14,15]), or the diffuse features are fitted to a broad peak-shape function to estimate the spin correlation length (see, e.g., [16]). However, the crystal structure plays no less significant a role in paramagnets than in ordered magnets: indeed, in a paramagnet the crystal structure completely determines the symmetry and periodicity of the diffuse scattering pattern [17].…”
Section: Introductionmentioning
confidence: 99%
“…The square of the order parameter calculated from the Brillouin function for an S = 2 system does not provide a good description of the ordering, however. The character of the transition is complicated by the geometrical frustration and evidence for significant spin fluctuations [3,40,53], but both the strain evolution and Figure 8. The strains e 1 , e 2 and e v as a function of temperature, calculated from lattice parameter data from Lee et al [35] using equation (1), shown against I 100 from Chatterji et al [13], with all data scaled to vary between 0 at T N and 1 at 0 K, as well as the square of the Brillouin function for an S = 2 system.…”
Section: Low Temperature Behaviourmentioning
confidence: 99%
“…The ordered moment decreases from 3.27 µ B at zero pressure to 1.52 µ B at 5 GPa. Kozlenko et al [14] and earlier, Park et al [31] attributed this to the concurrent existence of a spin liquid phase. This phase is also claimed to be responsible for the lowering of the ordered magnetic moment at zero pressure from the expected 4.0 µ B for (S = 2) Mn 3+ , as well as for the increase in diffuse scattering at the Néel temperature and at the applied pressure.…”
Section: Pressure Effect Of the Magnetic Order And Phase Transitionmentioning
confidence: 91%